Self-charging of the Eyjafjallajokull volcanic ash plume - Harrison, R; Nicoll, K; Ulanowski, Z; Mather, T (2010)
Volcanic plumes generate lightning from the electrification of plume particles. Volcanic plume charging at over 1200 km from its source was observed from in situ balloon sampling of the April 2010 Eyjafjallajökull plume over Scotland. Whilst upper and lower edge charging of a horizontal plume is expected from fair weather atmospheric electricity, the plume over Scotland showed sustained positive charge well beneath the upper plume edge. At these distances from the source, the charging cannot be a remnant of the eruption itself because of charge relaxation in the finite conductivity of atmospheric air. © 2010 IOP Publishing Ltd Printed in the UK.